Pendidikan Agama Kristen di Masa Lalu, Sekarang, dan di Masa Depan (International Forum of Researchers and Lecturers, 2024)
This article traces the evolution of Christian religious education from the past to the present, and projects its challenges and opportunities for the future. Through historical analysis, the article reveals how Christian religious education has adapted to the context of the times and current trends, including the influence of technology and globalization. The article also discusses the challenges faced, such as religious pluralism and changing moral values, and highlights the importance of adaptation and innovation so that Christian religious education remains relevant and effective in forming a generation of young people who are faithful and have noble character.